Forest restoration treatments increased growth and did not change survival of ponderosa pines in severe drought, Arizona - Fulé, Peter Z.; Meador, Andrew J. Sánchez; Moore, Margaret M.; Covington, W. Wallace; Kolb, Thomas E.; Huffman, David W.; Normandin, Donald P.; Roccaforte, John Paul (Ecological applications, 2022)
We report on survival and growth of ponderosa pines (Pinus ponderosa Douglas ex P. Lawson & C. Lawson) 2 decades after forest restoration treatments in the G. A. Pearson Natural Area, northern Arizona. Despite protection from harvest that conserved old trees, a dense forest susceptible to uncharacteristically severe disturbance had developed during more than a century of exclusion of the previous frequent surface-fire regime that ceased upon Euro-American settlement in approximately 1876. Trees were thinned in 1993 to emulate prefire-exclusion forest conditions, accumulated forest floor was removed, and surface fire was re-introduced at 4-years intervals (full restoration). There was also a partial restoration treatment consisting of thinning alone. Compared with untreated controls, mortality of old trees (mean age 243 years, maximum 462 years) differed by <1 tree ha−1 and old-tree survival was statistically indistinguishable between treatments (90.5% control, 92.3% full, 82.6% partial). Post-treatment growth as measured by basal area increment of both old (pre-1876) and young (post-1876) pines was significantly higher in both treatments than counterpart control trees for more than 2 decades following thinning. Drought meeting the definition of megadrought affected the region almost all the time since the onset of the experiment, including 3 years that were severely dry. Growth of all trees declined in the driest 3 years, but old and young treated trees had significantly less decline. Association of tree growth with temperature (negative correlation) and precipitation (positive correlation) was much weaker in treated trees, indicating that they may experience less growth decline from warmer, drier conditions predicted in future decades. Overall, tree responses after the first 2 decades following treatment suggest that forest restoration treatments have led to substantial, sustained improvement in the growth of old and young ponderosa pines without affecting old-tree survival, thereby improving resilience to a warming climate.